1973
DOI: 10.1159/000481053
|View full text |Cite
|
Sign up to set email alerts
|

Gluconeogenesis in the Newborn Rat: the Substrates and their Quantitative Significance

Abstract: The role assumed by gluconeogenesis in the metabolism of the neonatal rat and the evidence suggesting that this process is enhanced during the suckling period is discussed. The development of the enzymes and metabolic pathways implicated in gluconeogenesis from various potential precursors are reviewed; particular attention is given to their possible involvement under physiological conditions. The substrates considered are lactate, amino acids (particularly alanine, glutamine, serine, aspartate and hydroxyprol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

1974
1974
1986
1986

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 137 publications
3
16
0
Order By: Relevance
“…It is probable, in the normal fed or fasted adult rat, that the aminotransferase pathway plays a relatively minor role in gluconeogenesis from serine compared with the dehydratase pathway [6,15,16]. However, in the case of the neonatal rat it has been suggested that the role of the aminotransferase pathway might be considerably greater, and that the presence of a mitochondrial pathway of gluconeogenesis from serine might be important in terms of a neonatal mechanism for the conservation of the carbon skeleton of hydroxyproline, derived from collagen turnover in the rapidly-growing animal [6,1 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is probable, in the normal fed or fasted adult rat, that the aminotransferase pathway plays a relatively minor role in gluconeogenesis from serine compared with the dehydratase pathway [6,15,16]. However, in the case of the neonatal rat it has been suggested that the role of the aminotransferase pathway might be considerably greater, and that the presence of a mitochondrial pathway of gluconeogenesis from serine might be important in terms of a neonatal mechanism for the conservation of the carbon skeleton of hydroxyproline, derived from collagen turnover in the rapidly-growing animal [6,1 ].…”
Section: Resultsmentioning
confidence: 99%
“…There is good evidence that serine dehydratase (EC 4. 2.1.13), which catalyses the formation of pyruvate from serine, is involved in initiating gluconeogenesis in the adult rat (see [1]). Earlier studies suggested the presence of an alternative pathway that involved hydroxypyruvate rattler than pyruvate as an intermediate [2] and more recent work with isolated rat liver cells supports this conclusion [3].…”
Section: Introductionmentioning
confidence: 99%
“…The main changes induced by starvation with respect to adults were the increased levels of glutamate + glutamine and taurine, together with a strong decrease in hydroxyproline; this decrease could be related to the enhanced gluconeogenetic utilization of this amino acid during development (SNELL & WALKER, 1973).…”
Section: Discussionmentioning
confidence: 96%
“…Starvation induced a sharp increase in gluconeogenic ability on day 19 after birth in rats (WHITE & MILLER, 1976), this activation being, however, lower than in adults (SNELL & WALKER, 1973). This increase lowered lactate levels, not affecting those of glycerol, despite the increase found in adults with fasting (PALOU et al, 1981) because of enhanced lipolysis (KNOPP et d., 1970).…”
Section: Discussionmentioning
confidence: 98%
“…In the human, glycogen is present for the first time between the 15th and 25th weeks of gestation and increases markedly during the last month of pregnancy (Villee, 1953(Villee, , 1961. Liver glycogen decreases very abruptly after birth and remains low during the first days Snell and Walker, 1973). Most of the liver enzymes necessary for glycogenesis and gluconeogenesis are present at birth (Dawkins, 1963;Haworth, 1969).…”
Section: Liver Glycogenmentioning
confidence: 99%